Assessing the influence of matcha green tea extract on NF-κB/MAPK signaling pathway activation in rats: A study on irradiation-induced acute hepatic inflammatory response - Noha Sayed Hamed; Eithar K. El Adham; Amal I. Hassan (Phytomedicine Plus)
Background: Numerous forms of cancer are frequently treated with radiation therapy, which provides substantial benefits in tumor control. However, adverse effects, particularly the development of severe hepatitis, may render radiation therapy ineffective. Purpose: This study investigates the potential of matcha (M) green tea extract, a natural compound known for its high antioxidant properties and health-promoting properties, in a new approach to reduce radiation-induced liver damage. Study design and method: In this experimental investigation, the administration of M was conducted on female Wistar rats for duration of two weeks after gamma-ray irradiation. Next, a series of biochemical experiments were conducted to examine the impact of M on lipid peroxidation levels, antioxidant enzyme activities, and pro-inflammatory cytokines (IL-6, IL-10, and TNF-α) in liver tissue. The Western blot method was employed for this analysis. Liver miR-122 expression levels were determined using real-time reverse transcription polymerase chain reaction. In addition, the present study investigated the mechanism by which M stops the inflammatory process's crucial NF-κB/MAPK signaling. Results: This study suggests that the NF-κB/MAPK signaling pathway that triggers the radiation-induced inflammatory response is further inhibited by M making radiation therapy effective and safe. Conclusion: Further research in this area may reveal the underlying mechanisms and pave the way for the development of novel therapies for radiation therapy patients.